Risk Factors Associated with The Incidence of Diarrhea in Toddlers in The Working Area of The Pamenang Public Health Center - Lestari, Pujiah; Noerjoedianto, Dwi; Wisudariani, Evy; Ena Sari, Rumita; Lesmana S, Oka (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Diarrhea is the occurrence of defecation with a more liquid consistency than usual with a frequency of three times or even more within 24 hours. The incidence of diarrhea is related to factors such as water sources, toilet facilities, hand washing behavior, knowledge, and waste management. Objective: The aim of the study was to determine the risk factors associated with the incidence of diarrhea in toddlers in the working area of ??the Pamenang Health Center, Merangin Regency in 2022. Method: Using the chi-square method, the observational analytic case control approach. The sample in the study used a 1:1 ratio with a total sample of 85 cases and 85 control samples. Result and Discussion: The results of this study showed that the variable p-value of clean water was 0.001 with OR 0.146, the variable of toilet facilities was p-value 0.003 with OR 0.171, the variable of hand washing behavior was p-vacue 0.000 with OR 0.159, the mother's knowledge variable was p-value 0.017 with OR 0.292, landfill variable p-value 0.846 with OR 1.078. Conclusion: It can be concluded that there is a correlation between clean water sources, toilet facilities, hand washing behavior, mother's knowledge, and the incidence of diarrhea in toddlers in the working area of ??the Pamenang Health Center.